2011
DOI: 10.1007/s13191-011-0064-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of etchant variability on shear bond strength of all ceramic restorations - an in vitro study

Abstract: The present study was carried out to evaluate the effect of pre-luting surface treatments by 3 different etchant used at 3 different etching periods and their effect on shear bond strength of IPS Empress 2 luted to tooth by dual cure resin cement. Fifty samples of ceramic were divided into four groups as group I control group: No surface treatment, group II: Etched with Hydrofluoric (HF) acid (4.9%), group III: Etched with Ammonium bifluoride acid (9.4%) and group IV: Etched with Phosphoric acid (37%). Group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…The ceramic bonding systems are mainly mechano-chemical bonding between the luting cement and the ceramic surface [12]. Many studies had reported high bond strength of ceramics to dentin when the ceramics were treated by hydrofluoric acid [12], [14], [15]. This was in agreement with our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ceramic bonding systems are mainly mechano-chemical bonding between the luting cement and the ceramic surface [12]. Many studies had reported high bond strength of ceramics to dentin when the ceramics were treated by hydrofluoric acid [12], [14], [15]. This was in agreement with our study.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it offers an easy and time-saving technique to fabricate indirect esthetic restoration [11]. IPS Empress also has been used successfully for single unit restoration or even three units fixed bridge [12]. To improve the bond strength between indirect ceramic restoration and tooth structure, the silane coupling agent is advocated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainda que sejam ácido-sensíveis, tais cerâmicas apresentam diferenças estruturais e de composição, logo, a concentração do ácido e o tempo de condicionamento ideal variam entre elas. Para as vitrocerâmicas, há na literatura evidências de um padrão adequado de condicionamento obtido com HF em concentrações de 2,5% a 10%, aplicadas por períodos de 60 segundos a 3 minutos 25,29,33 . Para cerâmicas vítreas com baixo conteúdo de leucita, o condicionamento com HF a 9,5% por 60 segundos resultou em adequados valores de resistência de união 5,26 .…”
Section: Discussionunclassified
“…Segundo Passos et al (2009) e Soares et al (2005), o jateamento promove uma degradação não seletiva e aspereza ao compósito criando uma superfície irregular, removendo a matriz e expondo as fibras. Resultando, consequentemente, em uma melhor retenção ao cimento (SOARES et al, 2005;PATTANAIK;WADKAR, 2011).…”
Section: Discussionunclassified